Taxonomical notes on the long-clawed mole mice of the genus Geoxus (Cricetidae), with the description of a new species from an oceanic island of southern Chile - Teta, Pablo Vicente (2017)
The rodent genus Geoxus was largely considered as monotypic; however, a growing body of evidence suggests that this figure is incorrect. In this work, based on qualitative and quantitative morphological evidence and DNA sequence data, we reviewed the alpha taxonomy of this genus. Based on the examination of 134 specimens, four species are recognized within Geoxus: G. annectens(until recently referred to the genus Pearsonomys), G. michaelseni, G. valdivianus, and one species described herein as new. The four species have unique combinations of qualitative and quantitative morphological characters and were recovered as monophyletic using mitochondrial DNA sequences. The new species diagnosed and named here is endemic of Guafo Island, a small island of299 square kilometers on southern Pacific Chile. Phylogenetic analysis placed the new species as sister of G. michaelseni, a form widely distributed in southern Argentinean and Chilean Patagonia.